Preparación de la hoja de ajustes de auditoria del componente inventarios regulando la parte tributaria. - Santana Mora, Mercy Yolanda (My University, 2019)
The present investigation entitled "Preparation of the Audit Adjustment Sheet of the Inventories Component Regulating the Tax Part" is related to one of the most used procedures by the audit professionals in order to contribute to the evaluated company to the reasonable presentation of its financial statements, which are presented to internal and external users. For different purposes, the structure of the work consists of a history of surplus inventories. The pertinence of the work is related to the career of the accounting profession, which when solving the problem ends in the proposed adjustments in the audit and the objective that is proposed is the sheet of adjustments with the surplus of inventories, by means of the relation of the accounting data and the physical inspection performed by the auditor in order to report reasonable financial information and determine a correct tax application. Following are theoretical references adjustment sheet, audit, inventories, taxation, financial statements, which were consulted in scientific articles of high impact journals in the world of science to continue the case study, the main conclusion relates to the importance that the articles destined for sale enjoy adequate control and processing, taking into account that it is the main item that generates profitability for the trading companies.
La presente investigación titulada “Preparación de la Hoja de Ajustes de Auditoria del Componente Inventarios Regulando la parte Tributaria” se relaciona con uno de los procedimientos más utilizados por los profesionales de la auditoria con el fin de contribuir a la empresa evaluada a la presentación razonable de sus estados financieros, los cuales son presentados a usuarios internos y externos. Para distintos fines, la estructura del trabajo se compone de antecedentes del excedente de inventarios. La pertinencia del trabajo se relaciona con la carrera de la profesión contable que al resolver el problema termina en los ajustes propuestos en la auditoria y el objetivo que se propone es la hoja de ajustes con el excedente de inventarios, mediante la relación de los datos contables y la inspección física realizada por el auditor a fin de que se reporte información financiera razonable y se determine una correcta aplicación tributaria. Seguidamente se presentan referentes teóricos hoja de ajustes, auditoria, inventarios, tribulación , estados financieros, que fueron consultados en artículos científicos de revistas de alto impacto en el mundo de la ciencia para proseguir con el caso práctico, la principal conclusión hace relación a la importancia de que los artículos destinados para la venta gocen de un control y procesamiento adecuado, teniendo en cuenta que se trate del principal rubro que genera rentabilidad para las empresas comercializadoras.
Keywords: HOJA DE AJUSTES; AUDITORIA; INVENTARIOS; TRIBUTACIÓN; ESTADOS FINANCIEROS